2006
DOI: 10.1016/j.paid.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual biases and positive schizotypy: The role of perceptual load

Abstract: The study investigated the effects of perceptual load on the bias to report seeing non-existing events-a bias associated with positive symptoms of schizophrenia and positive schizotypal symptoms. Undergraduate students completed psychometric measures of schizotypy and were asked to detect fast moving words among non-words under different levels of perceptual load. Perceptual load was manipulated through stimulus motion. Overall, the results showed that the higher the perceptual load, the stronger the bias to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
2
16
1
1
Order By: Relevance
“…The present result findings replicate and extend evidence from studies that have employed auditory stimuli (Bentall & Slade, 1985;Rankin & O' Carroll, 1995), as well as in other paradigms that employed abstract visual stimuli (Feelgood & Rantzen, 1994;Jakes & Hemsley, 1986). The obtained results also concur with similar findings from different word detection paradigms (Tsakanikos, 2006;Tsakanikos & Reed, 2005a;2005b).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present result findings replicate and extend evidence from studies that have employed auditory stimuli (Bentall & Slade, 1985;Rankin & O' Carroll, 1995), as well as in other paradigms that employed abstract visual stimuli (Feelgood & Rantzen, 1994;Jakes & Hemsley, 1986). The obtained results also concur with similar findings from different word detection paradigms (Tsakanikos, 2006;Tsakanikos & Reed, 2005a;2005b).…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that perceptual ambiguity, at least in the way it was manipulated in this experiment, was not critical in the generation of schizotypal biases. However, it has been recently demonstrated in a different detection-of-fast-moving-words paradigm (Tsakanikos, 2006) that, although speed of stimulus presentation increased, the number of false perceptions in all participants (as in the present study) were predicted by schizotypy only when the speed was 9 frames/s, but not under conditions of lower speed of 7 frames/s and higher speed of 11 frames/s, suggesting that the amount of perceptual ambiguity was critically involved in the generation of schizotypal biases. This partial discrepancy might be due to the different methods employed to manipulate perceptual ambiguity through stimulus presentation (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more accurate understanding of the contribution of perception load in psychotic symptomatology could also benefit cognitive-behavioural psychotherapeutic interventions. A study on the effects of perceptual load on bias generation associated with schizotypal traits (Tsakanikos, 2006) found that overall perceptual biases were a positive function of perceptual load, although psychotic-like perceptual biases were only observed under conditions of medium perceptual load. Tsakanikos hypothesises that, if such cognitive biases were responsible for the maintenance of certain positive symptoms of schizophrenia, a voluntary increase in perceptual load (namely carrying out a cognitively demanding task during a hallucinatory experience) could have a detrimental effect on the intensity of such symptoms and that the identification of parameters that modulate perceptual biases in clinical practice could enhance our understanding about the formation and the maintenance of hallucinations.…”
Section: Discussionmentioning
confidence: 99%
“…A téveszme-és/vagy hallucinációszerű élményekről beszámoló egészséges személyek fogékonyak arra, hogy értelmetlen karakterláncokban értelmes szavakat észleljenek (GRANT, BAL-SER, MUNK, LINDER és HENNIG, 2014;REED és mtsai, 2008;TSAKANIKOS, 2006;TSAKANIKOS és REED, 2005), háromszögek véletlenszerű mozgását szabályosnak ítéljék és a háromszögeknek szándékot tulajdonítsanak (FYFE, WILLIAMS, MASON és PICKUP, 2008), vagy vizuális (SIMMONDS-MOORE, 2014) és auditoros zajban értelmes észleleteket tapasztaljanak meg (GALDOS és mtsai, 2011;SIMMONDS-MOORE, 2014). Ezek a tendenciák kedvezőtlen esetben pszichotikus tünetekhez vezethetnek (például GALDOS és mtsai, 2011), de akár utat nyithatnak kreatív meglátásoknak: aki képes rendszert látni abban, ami mások számára véletlenszerű zaj (DEYOUNG és mtsai, 2012;FYFE és mtsai, 2008;GRANT és mtsai, 2014), az új összefüggéseket fedezhet fel (MEDNICK, 1962).…”
Section: Dopaminfüggő Alapvető Kognitív Folyamatok éS Egyéni Különbséunclassified